The Effect of Unreliable Machine for Two Echelons Deteriorating Inventory Model - I Nyoman Sutapa; I Gede Agus Widyadana (Jurnal Teknik Industri, 2014)
Many researchers have developed two echelons supply chain, however only few of them consider deteriorating items and unreliable machine in their models In this paper, we develop an inventory deteriorating model for two echelons supply chain with unreliable machine. The unreliable machine time is assumed uniformly distributed. The model is solved using simple heuristic since a closed form model can not be derived. A numerical example is used to show how the model works. A sensitivity analysis is conducted to show effect of different lost sales cost in the model. The result shows that increasing lost sales cost will increase both manufacture and buyer costs however buyer’s total cost increase higher than manufacture’s total cost as manufacture’s machine is more unreliable.